The expense of energy expended (calories) during the studied physical education for primary schools. - Talaat, Firas; Masiar, Ali (Journal of Physical Education, 2014)
There are advanced countries devoted its research and worked all their ability to raise the level of physical activity for students during the studied physical education in ways that advanced scientific and proper planning as it can through which energy investment instudents, and the lies the importance of searching through studied physical education can increase physical activity among students in a scientific thoughtful and not random irregular, and the objective of this research to know the energy expended and the number of meters harvested for research sample during the studied Physical Education, and the researchers used the descriptive style relay, was chosen as the research sample way intentional students from the fifth primary, totaling 58 students, and have concluded the researchers to measure the energy expended and the number of meters Mileage helped to know what make him lose a student of calories during the lesson and Kilometers which, in addition to the lack of interest in studying physical education dramatically by educators lead to not to raise the level of physical activity, and was the most important recommendations concern the exercise of physical activity in primary schools according to the basis of sound scientific , relying on physical education lesson dramatically in order to raise the level of physical activity for students